Effect of water deficits on the growth and secondary metabolites of Salvia dolomitica Codd. and Salvia namaensis Schinz - Shaheed Roos; Felix Nchu (AOSIS, 2021)
Background: Salvia dolomitica Codd. and Salvia namaensis Schinz. are indigenous to southern Africa and are used as medicinal plants in folk medicine. Aim: This study aimed to assess the effects of different levels of water deficit treatments on the growth, concentration of secondary metabolites, and anti-Fusarium oxysporum activity of S. dolomitica and S. namaensis. Setting: Experiments were carried out on the Bellville campus of the Cape Peninsula University of Technology, Cape Town. Methods: Four weeks old seedlings of the two species were subjected to 3-, 6-, 9- and 12-day water deficit regimes. Secondary metabolites such as polyphenols, alkaloids, and flavanols were assessed using spectroscopic methods. The anti-fungal activities of crude extracts obtained from plants were evaluated in a micro-dilution bioassay. Results: In all treatments, the plant height, crown width, number of stems and leaves, and fresh and dry weights reduced with increased water deficits. Acetone extracts from all treatments showed anti-fungal activity. However, extracts from the treatment with moderate water deficit (6-day watering interval) recorded significantly (P 0.01) better inhibition of F. oxysporum at the 18 h post incubation than the commercial fungicide, Mancozeb. Conclusion: This research has revealed that mild to moderate water deficit level favours the accumulation of alkaloids in S. dolomitica. Meanwhile, mild to severe water deficit significantly lowered flavanol content in S. namaensis. There was a correlation between the increase in total alkaloid contents and the enhanced anti-fungal activity of extracts of S. dolomitica. The present findings pave the way for optimised cultivation of medicinal plants and development of bioactive natural products.